2019
DOI: 10.13189/cea.2019.070302
|View full text |Cite
|
Sign up to set email alerts
|

Home-school Travel: Analysis of Factors Affecting Italian Parents' Mode Choice

Abstract: Pedestrian injury is a major hazard to the health of children in most developed countries. Pedestrian accidents are one of the first causes of injury-related deaths and hospitalizations among children aged 5 to 14 in industrialized countries. This study has a dual objective: 1) to identify the factors affecting Italian parents' propensity to use private cars to accompany their children to school; 2) to analyze the availability of Italian parents to let their children walk to school alone. In order to develop t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The study also reinforced an already established fact that Italian children gain independent mobility during school years to a smaller extent than children in the rest of Europe, in this case Croatia [5,6]. While in Rijeka and Osijek respectively 6% and 11% of children were supervised by an adult while crossing the street, in Enna the percentage of supervised children was 55%.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The study also reinforced an already established fact that Italian children gain independent mobility during school years to a smaller extent than children in the rest of Europe, in this case Croatia [5,6]. While in Rijeka and Osijek respectively 6% and 11% of children were supervised by an adult while crossing the street, in Enna the percentage of supervised children was 55%.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, most at risk of traffic accidents are boys aged from 11 to 14 years. In Italy, many children are accompanied by their parents on daily travel to and from school [5]. On average only one third of children go to school without adult company when the walking distance is up to 1 km-precisely 33.2% of children up to 14 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…), cause significant reductions of speeds, of accidents and of the severity of the accidents themselves (Fernandes et al, 2018, Nicholson et al, 2014. Recent studies also confirmed that the effectiveness of traffic calming measures can also induce transport mode choices alternative to motor vehicles, favouring sustainable transport modes such as cycling and walking (Gössling et al, 2019, Distefano et al, 2019c, Vasudevan and Patel, 2017, Nicholson et al, 2014.…”
Section: Discussionmentioning
confidence: 89%
“…Main purpose of this stage: establish a long term post-participatory strategy observation and data gathering system [7] to evaluate users' engagement and satisfaction with results for a long term duration.…”
Section: Fifth Stage: Completion Of Design and Constructionmentioning
confidence: 99%